Impact of heating operations on the microbial ecology of foods - Xanthakis, Epameinondas; Valdramidis, Vasilis Panagiotis (My University, 2017)
There are several drawbacks of heat processes as their application may also lead to nutritional and quality deterioration of the food product. The chapter presents basic information regarding the heating processes and unit operations and covers the impact of these operations on food-borne microorganisms. It describes the main cooking methods, such as grilling, broiling, and roasting. Quantitative methodologies are the main tools to describe the impact of a process as well as the storage conditions post-processing on the food stability. In order to assess the efficacy of a specific processing technology, the estimation of the time to achieve a certain number of log reductions can be applied. The most common process in the food industry is the thermal process. The chapter reviews a number of different thermal processes and outlines critical issues in relation to their efficacy and to their impact on the microbial inactivation.
Keywords: Cooking methods; Food industry; Food stability; Food-borne microorganisms; Heating processes; Microbial ecology; Microbial inactivation; Nutritional properties; Quantitative microbiology; Thermal processes